Quantificação dos metabólitos do albendazol em plasma bovino por cromatografia líquida quiral de alta eficiência, com injeção direta de amostras - Belaz, Katia Roberta Anacleto (2007)
This work presents the development and validation of a sensitive and enantioselective multidimensional high performance liquid chromatography (HPLC) method for determination of albendazole metabolites: albendazole sulphoxide, chiral compound, albendazole sulphone and albendazole 2-aminesulphone in bovine plasma. The compounds, (±)- albendazole sulphoxide, albendazole sulphone and 2-aminesulphone were extracted from bovine plasma using a octyl restricted access media bovine serum albumin column (C8-RAM-BSA) (5.0 x 0.46 cm i.d.) and analyzed on a chiral column containing amylose tris(3,5-dimethylphenylcarbamate) coated onto APS-Nucleosil support, as stationary phase (15.0 x 0.46 cm i.d.). The chromatographic separations of all target compounds were achieved using a mobile phase composed of phosphate buffer (0.01 M; pH 7.5):acetonitrile (60:40 v/v), flow rate of 0.5 mL/min and fluorescence detection at 290 nm and 320 nm, excitation and emission, respectively. The calibration curves were linear in the concentration range of 40.00-1280 ng/ml for each albendazole sulphoxide enantiomer, 10.0-320 ng/mL for albendazole sulphone and 10.0-320 ng/mL for albendazole 2-aminesulphone. The validated method showed linearity, precision, accuracy and adequate sensitivity, allowing it to be appropriate for pharmacokinetics studies after administration of albendazole by different routes. Moreover, two metabolites of albendazole, the albendazole sulphoxide and albendazole sulphone, were synthesized by oxidation reaction using the aquo(N-oxo of piridine) molybdenum (VI) oxo diperoxo complexe.